Association Between Echocardiographic Non-invasive Myocardial Work Indices and Myocardial Fibrosis in Patients With Dilated Cardiomyopathy - Cui, Cunying; Li, Yanan; Liu, Yuanyuan; Huang, Danqing; Hu, Yanbin; Wang, Ying; Ma, Lijia; Liu, Lin (Frontiers in Cardiovascular Medicine, 2021)
Objectives: To analyze the association between global myocardial work indices evaluated by noninvasive left ventricular (LV) pressure-strain loop (PSL) and LV myocardial fibrosis in patients with dilated cardiomyopathy (DCM). Methods: A total of 57 patients with DCM were included in this prospective study. Global work index (GWI), global constructive work (GCW), global wasted work (GWW), global work efficiency (GWE) and global longitudinal strain (GLS) were measured using LVPSL. LV volumes and LV ejection fraction (LVEF) were evaluated using cardiac magnetic resonance imaging (CMRI), LV myocardial fibrosis was estimated at CMRI by qualitative assessment of late gadolinium enhancement (LGE). According to the CMRI, the studied population was divided into two groups, namely: patients without LGE (LGE-) and patients with LGE (LGE+). Results: The LGE+ group presented with increased age, LV end systolic volume (LVESV) index and reduced GWI, GCW, GWE, GLS, CMRI-derived LVEF (LVEFCMRI), the differences between the two groups were statistically significant (P＜0.05). After correcting for age and LVESV index, LVEFCMRI, GLS, GWI, GCW, and GWE retained independent associations with LV myocardial fibrosis. According to receiver operating characteristics (ROC) analysis, LVEFCMRI, and GCW showed larger AUC and higher accuracy , sensitivity, and specificity than GLS, the accuracy of predicting LV myocardial fibrosis ranged from high to low as: LVEFCMRI, GCW, GWE, GWI, and GLS. Conclusions: LVEFCMRI, GWI, GCW, GWE, and GLS remained significant predictors of LV myocardial fibrosis. LVEFCMRI, and GCW appeared to better predict LV myocardial fibrosis compared with GLS.